PRODUK HUKUM NASKAH AKADEMIK UNTUK KENDARAAN RAKITAN BEROPERASI DI JALAN - Arief, Sofyan (Al-Qisth Law Review, 2017)
Gerandong currently is illegal vehicles circulating in the community, namely motor vehicles used for mobile rice mill facility by people who operate on the highway. The problem faced is the need for cheap transport of agricultural field of the community, while there are low-tech impact on the feasibility of operating licenses as a vehicle that runs on the highway, security levels, and pollution. Based on these problems Gerandong vehicle license ban needs to be solved in a comprehensive and integrated from upstream to downstream, in order to provide economic benefits, the development of science and technology for society, and safe for the environment. Gerandong management regulations are needed to ensure legal certainty, clarity of responsibility and authority of the government, and the role of society and the business world, so gerandong as an alternative vehicle for agriculture are proportional to run effectively and efficiently.